1987
DOI: 10.1016/0378-1097(87)90013-9
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide breakdown by mixed populations of human faecal bacteria

Abstract: Measurements of polysaccharide‐degrading activity in different fractions of human faeces showed that bacterial polysaccharidases and glycosidases were primarily associated with the washed bacterial fractions. Amylase, pectinase and xylanase were the major polysaccharide‐hydrolysing enzymes detected, whilst α‐L‐arabinofuranosidase, β‐D‐xylosidase, β‐D‐galactosidase and β‐D‐glucosidase were the most active glycosidases. Starch and 3 non‐starch polysaccharides (NSP; pectin, xylan and arabinogalactan) were ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 22 publications
10
89
1
3
Order By: Relevance
“…Vince and colleagues [11] also did not find increases in fecal short-chain fatty acid production following arabinogalactan consumption. However, their work as well as the work of Englyst and colleagues [12] did report increases in SCFA production following arabinogalactan supplementation of fecal incubates.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vince and colleagues [11] also did not find increases in fecal short-chain fatty acid production following arabinogalactan consumption. However, their work as well as the work of Englyst and colleagues [12] did report increases in SCFA production following arabinogalactan supplementation of fecal incubates.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, arabinogalactan is fermented at a slower rate than other carbohydrates due to its branched structure [12]. Fermentation is evidenced by the ability of human intestinal microflora to degrade arabinogalactan and produce short-chain fatty acids [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that the fecal bacterial fractions we obtained might contain a low number of bacteria coming from solid-associated bacterial population, which has dominant role in the fiber digestion of herbivorous mammals. Alternatively, the washing procedure during preparation of bacterial fraction might be responsible for removal of the extracellular CM-cellulase activity (Englyst et al 1987). On the contrary, total fecal specific CM-cellulase activity was similar to respective specific activity of rumen solid-associated bacteria (Martin et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…15 It has been suggested that RS promotes higher colonic levels of butyric acid than other sources of indigestible carbohydrates. 16,17 Furthermore, RS from different sources seems to vary in the proportion of SCFA formed. In rat models, fermentation of potato starch has produced comparatively high amounts of butyric acid.…”
Section: Introductionmentioning
confidence: 99%